PENGARUH MODEL PEMBELAJARAN MIND MAPPING TERHADAP HASIL BELAJAR SISWA PADA SUBTEMA 3 PERISTIWA MENGISI KEMERDEKAAN DIKELAS V SDN 01 SITIUNG - Muhammad Subhan; Lika Apreasta; Dika Ariyani (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
This research was driven by the desire to investigate the impact of subtheme 3 on student learning outcomes. Even though independence activities have been carried out, there are still many fifth grade students at SDN 01 Sitiung who have not achieved Minimum Competency (KKM), especially in the sciences field, especially theme 7 sub-theme 3. This research seeks to determine the effect of the Mind Mapping learning approach on student academic achievement by comparing their learning outcomes before and after its implementation.This type of research is a Pre-Experimental Design with a One-Group Pretest-Posttest Design. The population of class I-VI students at SDN 01 Sitiung, the sample used by class V students at SDN 01 Sitiung was 25 people. The data collection method used in this research is saturated sampling. The use of written test techniques, especially test sheets, for data collection purposes is a common practice in educational research. The statistical analysis methodology used in this study includes the Normality test and Hypothesis test using SPSS..The results of the analysis of the hypothesis test data on the paired sample test with a significant level of 0.05, show that the sig (2-tailed) result is smaller than the test data or equation 0.002 <0.05, then H0 is rejected. The criteria for testing the hypothesis, it was concluded that there was a significant influence of the Mind Mapping learning model on the learning outcomes of sub-theme 3 science material in class V SDN 01 Sitiung.